Generation Y As Organ Donor: Informational And Supportive Influence Of Socialization Agents On Attitude Towards Organ Donation - Maniam, Pushpavalli; Zolkepli, Izzal Asnira (2015)
Organ donation is a health issue which involves a process of an individual freely giving consent to donate organs or tissue for very ill or dying recipients. In Malaysia, the notion of organ donation has been facilitated by many government authorities since 1970s. However, recent statistics show that the number of patients requiring donated organs far outnumbers the donors. The unwillingness to donate is commonly associated with spiritual beliefs, myths, misunderstanding, lack of knowledge and lack of trust. Most of the studies conducted in Malaysia highlighted the reasons impeding Malaysians to become donors rather than looking at the aspect of communication that influences the attitude of the potential organ donor. Thus, this study is designed to focus on the values and norms which are commonly transmitted by the socialization agents that consist of parents, peers, educational institution, traditional mass media and new media, which are presumed to have significant effects on behaviour development of the potential donor towards organ donation. Particularly, this research attempted to examine the influence of these socialization agents on Generation Y’s attitude formation towards organ donation. Generation Y was selected based on the conclusion made by previous scholars that this group of individuals is at the stage of discovering themselves on how to fit into society and the social world, where they mostly consume ideas from their socialization agents to achieve their life goals. The study employed quantitative method using survey questionnaire. Individuals were chosen based on non-probability sampling and the age range was between 18-24 years old. The socialization agents were measured in terms of informational and supportive influence. The findings of this study indicated that the supportive influence from all the agents of socialization affected the attitude of Generation Y and parents appeared as the most influential agent. However, their attitude was negatively correlated with the intention to sign up as an organ donor. The implications for social marketers were also discussed.